Perlindungan Hukum terhadap Konsumen yang Mendapatkan Iklan Menyesatkan yang Beredar di Platform Digital Media Sosial: Studi Kasus Putusan Mahkamah Agung Nomor 659 K/Pdt.Sus/2012 - Deltalivia Anggraiyani, (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study analyzes the forms of business actors’ liability, legal protection for consumers, and the responsibilities of digital platform providers in relation to the circulation of misleading advertisements on social media. The dissemination of misleading advertisements within the consumer protection context creates an imbalance between business actors and consumers, placing consumers in a disadvantaged position. Although the Consumer Protection Law No. 8 of 1999, Government Regulations, and Ministerial Regulations related to advertising and digital platforms affirm consumers’ rights to accurate, clear, and honest information, as well as the obligation of business actors and advertisers to refrain from providing misleading information, in practice business actors often lack transparency in conveying product information, thereby harming consumers. This study employs a normative legal method using a statutory approach. The main findings indicate that the spread of misleading advertisements obscures the essence of consumer protection and results in tangible harm to consumers. Therefore, strengthening regulations and implementing stricter oversight mechanisms for both business actors and digital platform providers are necessary. Law enforcement should focus on imposing effective sanctions to create a deterrent effect, while ensuring fast access to compensation for consumers in accordance with the principles of consumer protection.